Educational Game Analysis Using Playcentric Approach - Asrullah Ahmad (Jurnal Titik Imaji, 2021)
Game have become very popular among the wider community, especially for users of smart phone devices. Game on a smart device are also often used as an effective aid for children's learning processes, of course with parental assistance and guidance. This should be seen as a potential that can be utilized by a gim developer in designing a gim. Therefore, in this study, educational game that are successful in the market are structurally dissected using the gim design method, namely the Playcentric Approach, which is then juxtaposed with the MDA Framework gim design method. The research was conducted in a descriptive qualitative form which then resulted in an analysis that described the standard structure of an educational gim which would certainly be very useful for the purposes of gim studies and educational gim design.Keywords: Educational Gim, MDA Framework, Playcentric